Interpretive structural modeling (ISM) of risk management in Iran's construction industry - Hamed Shokri; Abbas Afrazeh (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Investment in the construction industry can only cause economic growth and achieve economic results when capital injection and housing production are targeted and ultimately lead to housing consumption; because if the imported funds are not directed to the building sector, the final price of housing will increase and will make real consumers less able to buy. Therefore, the entry of liquidity into the construction industry requires formulation of strategy and policy in order to increase the growth rate of housing. Also, risk management and knowing its key components lead to reducing construction costs and creating a more appropriate price in the construction industry. The aim of the current research is to know the dimensions and components of risk management in Iran's construction industry with a fuzzy Delphi approach with interpretive structural modeling and DEMATEL technique.Methodology: The current research method is exploratory and the goal is to answer the research questions. In terms of the type of research, it is practical because its results are used for risk management in Iran's construction industry. The method of the current research is mixed (qualitative-quantitative). In the qualitative dimension, using the fuzzy Delphi method, it has identified the dimensions and components of risk management in the construction industry in Iran. In the quantitative dimension, by using interpretative structural modeling technique and DEMATEL, by using surveys of experts and university professors, it has been done to stratify and examine the intensity of relationships between dimensions.Findings: The results show that at the lowest level of the model (level three), the risk dimension of political factors is placed, which acts as the cornerstone of the model and to achieve risk management in projects. Iran's construction should start from this factor. Also, the results of examining the intensity of relationships between dimensions with Dimetal show that the social risk dimension is the most effective dimension, has the highest numerical value based on the row sum (D), and thus, with the most influential dimension among the investigated dimensions of risk management in Iran's construction industry has been identified. Also, according to (D-R), the lowest value, the risk dimension of laws and regulations, is the most effective dimension of risk management in Iran's construction industry.Originality/Value: The current research is new in terms of the subject area, i.e. in the field of the construction industry of Iran, and in terms of the location area, i.e. companies active in the field of the construction industry of New Tehran. The research gap that creates the space for innovation in the current research, according to the perspective of soft operations research, which is a tool for creating complex and new problems, is the use of Interpretive Structural Modeling (ISM) and DEMATEL. Less research has been done on leveling and examining the intensity of impact and effectiveness of the components of risks in the construction industry.